The UBC9/SUMO pathway affects E-cadherin cleavage in HPV-positive head and neck cancer - Sabatini, Maria Elisa; Compagnoni, Micaela; Maffini, Fausto; Miccolo, Claudia; Pagni, Fabio; Lombardi, Mariano; Brambilla, Virginia; Lepanto, Daniela; Tagliabue, Marta; Ansarin, Mohssen; Citro, Simona; Chiocca, Susanna (Frontiers in Molecular Biosciences, 2022)
Functional loss of E-cadherin is frequent during tumour progression and occurs through a variety of mechanisms, including proteolytic cleavage. E-cadherin downregulation leads to a conversion to a more malignant phenotype promoting Epithelial to Mesenchymal Transition (EMT). The UBC9/SUMO pathway has been also shown to be involved in the regulation of EMT in different cancers. Here we found an increased expression of UBC9 in the progression of Head and Neck Cancer (HNC) and uncovered a role for UBC9/SUMO in hampering the HPV-mediated E-cadherin cleavage in HNC.